Production of carotenoids by Rhodotorula toruloides isolated from Brazilian tropical savannah - Machado, W. R. M. [UNESP]; Silva, L. G. [UNESP]; Vanzela, E. S. L. [UNESP]; Del Bianchi, V. L. [UNESP] (Univ Putra Malaysia Press, 2019)
Several artificial colouring agents are used as food additives to improve the foods' visual appearance. A recent increase in the use of natural colouring with bioactive properties (antioxidants) as a substitute for additives used in the food industry has led to the search for novel sources to produce such substances with functional colouring. The present work was aimed to isolate and select yeasts from the Cerrado (Savannah) biome (Central region, Brazil) to produce carotenoids. Sixty-nine of the 470 colonies, selected after screening, presented colours from yellow to red. These yeasts were grouped into three colours: yellow, pink and orange. Yeast belonging to the pink group, identified as Rhodotorula toruloides, was chosen for improvement of the factors (physical and nutritional) involved in submerged cultivation. Carotenoid bioproduction was improved by using an experimental design which evaluated the characteristics of the physical processes (agitation and temperature), followed by 2(5-1) factorial experimental design to select the relevant factors for the culture medium. Following statistical analysis, a complete second-order experimental design was employed to optimise the composition of the culture medium. The maximum carotenoid production obtained was 1,333.11 mu g.L-1 (106.92 mu g.g(-1)) after 144 h at 25 degrees C and 130 rpm in yeast malt (YM) medium containing 45.95 g.L-1 glucose, 1 g.L-1 malt extract, 0.7 g.L-1 yeast extract, and 0.4 g.L-1 peptone, with an initial pH value of 6. This result showed the potential of this yeast as a viable source of biopigments. (C) All Rights Reserved
Keywords: Pigmented yeast; beta-carotene; Factorial design; Optimisation; Rhodotorula toruloides